PENINGKATAN HASIL BELAJAR PESERTA DIDIK PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) BERBANTUAN GOOGLE SITES DI KELAS IV SDN 04 TERANDAM KOTA PADANG - Rizkina Julvi, Hazila; Arwin Rasyid; Yeni Erita; Ranti Meizatri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in Pancasila Education learning in grade IV of SDN 04 Terandam, Padang City, which is indicated by the majority of students not having achieved the Learning Objective Achievement Criteria (KKTP). This problem is caused by the lack of active student involvement, the use of less varied learning models, and the less than optimal use of learning media. This study aims to describe the improvement in student learning outcomes through the implementation of the Team Games Tournament (TGT) cooperative model assisted by Google Sites. This type of research is Classroom Action Research (CAR) with a qualitative and quantitative approach carried out in two cycles, including planning, implementation, observation, and reflection. The research subjects were 26 grade IV students. Data collection techniques used tests and non-tests, while data analysis was carried out qualitatively and quantitatively. The results of the study showed an increase in every aspect. The value of the teaching module increased from 91.8 to 98.28. Teacher activity increased from 87.46 to 96.42, and student activity from 83.89 to 96.42. Student learning outcomes also increased, namely in the attitude aspect from 76.21 to 87.01, knowledge from 81.34 to 90.38, and skills from 79.32 to 90.98. It can be concluded that the implementation of the Team Games Tournament (TGT) model assisted by Google Sites is effective in improving student learning outcomes in Pancasila Education learning in grade IV.